Fabrication and characterization of a new-style structure capillary channel in reaction bonded silicon carbide composites. Issue 7 (July 2017) - Song, Suocheng; Bao, Chonggao; Ma, Yana; Wang, Keke
Highlights: A new-style structure capillary channel was fabricated. Large numbers of nano-sized SiC grains were produced. The size of the residual silicon phase was nano-sized. The residual silicon volume fraction was 4.0%. Abstract: A new-style structure capillary channel was fabricated by using boron carbide powder mixtures with an appropriate multimodal particle size distribution to promote the liquid silicon infiltration in reaction bonded silicon carbide composites. Two types of core–rim structure were observed and the secondary SiC produced in the siliconisation reaction existed in two forms: nucleating on the original SiC and occupying the original positions of the residual silicon. The size of the secondary SiC in the latter form was in a range of tens to hundreds nanometers. These nano-sized SiC grains and the additive of fine boron carbide particles refined the crystalline structure and broke up the residual silicon phase into small pieces. Using this method, the microstructure was refined and the mechanical properties improved significantly. The lowest residual silicon volume fraction was 4.0% and the flexural strength and fracture toughness reached peak values of 526 ± 21 MPa and 6.2 ± 0.4MPa m 1/2, respectively.